2010
DOI: 10.1074/jbc.m109.074310
|View full text |Cite
|
Sign up to set email alerts
|

Glucose 6-Phosphate Accumulation in Mycobacteria

Abstract: Glucose 6-phosphate (G6P) is a metabolic intermediate with many possible cellular fates. In mycobacteria, G6P is a substrate for an enzyme, F 420 -dependent glucose-6-phosphate dehydrogenase (Fgd), found in few bacterial genera. Intracellular G6P levels in six Mycobacterium sp. were remarkably higher (ϳ17-130-fold) than Escherichia coli and Bacillus megaterium. The high G6P level in Mycobacterium smegmatis may result from 10 -25-fold higher activity of the gluconeogenic enzyme fructose-1,6-bisphosphatase when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 38 publications
1
58
0
Order By: Relevance
“…However, this hypothesis has yet to be supported with data on phenotypes or energy, and it remains unclear whether purified FDOR-As are capable of reducing menaquinone (30,32). There is also evidence that mycobacteria instead use electrons liberated from G6P by Fgd to directly detoxify exogenous agents (363). Two independent studies have demonstrated that FDOR-As rapidly reduce menadione and plumbagin using F 420 H 2 (30,32), and it is also plausible that these highly promiscuous proteins (28,55) can directly detoxify certain antibiotics too.…”
Section: Mycobacteriamentioning
confidence: 82%
See 4 more Smart Citations
“…However, this hypothesis has yet to be supported with data on phenotypes or energy, and it remains unclear whether purified FDOR-As are capable of reducing menaquinone (30,32). There is also evidence that mycobacteria instead use electrons liberated from G6P by Fgd to directly detoxify exogenous agents (363). Two independent studies have demonstrated that FDOR-As rapidly reduce menadione and plumbagin using F 420 H 2 (30,32), and it is also plausible that these highly promiscuous proteins (28,55) can directly detoxify certain antibiotics too.…”
Section: Mycobacteriamentioning
confidence: 82%
“…The survival rate of ⌬fbiC strains of M. tuberculosis is 100-to 1,000-fold lower than wild-type cells following challenge with redox cycling agents (i.e., menadione, plumbagin) and antibiotics (i.e., isoniazid, clofazimine) (32). ⌬fgd strains of M. smegmatis are similarly impaired (363). One explanation is that mycobacteria store electrons as glucose-6-phosphate (G6P) and mobilize them using Fgd (F 420 -dependent glucose-6-phosphate dehydrogenase) in response to oxidative stress; G6P levels in M. smegmatis are consistently approximately 100-fold higher than those of E. coli during preferential growth conditions, but the levels become depleted following challenge with redox cycling agents (363).…”
Section: Mycobacteriamentioning
confidence: 94%
See 3 more Smart Citations